Fact-checking and health: an analysis of GaúchaZH's "Verdade ou Boato (Truth or Rumor)" section - Gruszynski, Ana (2020)
This article analyses the ‘Verdade ou Boato’ (Truth or Hoax) section, published in the newspaper Zero Hora (printed medium) and in GaúchaZH (digital medium), aiming: to understand the characteristics of the articles published in that section and the profie of information evaluated in it; and to discuss how publishers cope with their position of credibility in the face of the modes of production and circulation of content changes brought by the digital environment, especially with regard to health issues. The bibliographic review and documentary researches and the content analysis of a corpus composed of 25 articles constitute the methodological procedures for analyse them. The result reveals that the fact-checking initiative reinforces journalism as an expert system. Among the characteristics identifid, we highlight the adaptation of the headlines to deny false information. In the digital edition one can observe the little use of the potential of hypertext to compose a narrative supported by evidences.